Karakteristik Nilai Kuat Tekan Bebas Stabilisasi Semen Tanah CL-ML Terhadap Siklus Pembahasan Pengeringan - Dodi Pratama; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The soil that classified as CL-ML soil have range of plasticity index around 4% s/d 7%, and liquid limit with range 12% s/d 30% according to the Casagrande Plasticity graph, this soil condition is very susceptible to the addition of water content so that cause soil at winter season being easily melted as a porridge and cracked as of existed at retrieval specimen location at dry season. This retrieval specimen location located at Government Office of Pekanbaru Area, Indonesia. This situation being problem if there is construction work above it such as road construction. Soil restoration is necessary for stabilizing soil. In this case used stabilizing soil chemically. Ihis research focuses to cycle process of wet-dry toward soil mechanical characterize effect that stabilized by cement. This research result showed that value of unconfined compressive strength toward wet-dry cycle have different values. Cement addition to CL-ML soil get very significant increasing of unconfined compressive strength. Highest increasing unconfined compressive strength is on 7 days curing, 3x 24 hours, drying second cycle about 1.636,51 kPa, this thing caused by cement that contained in 7 days cured soil reacted and turned into paste dan eventually cement that contained in soil start hardened, so that is able to increasing unconfined compressive strength value high enough.Keywords: Wet-dry cycle, UCS, CL-ML, cement stabilization.